BOARD CHARACTERISTICS AND FIRM PERFORMANCE OF SELECTED INSURANCE COMPANIES LISTED IN NIGERIAN EXCHANGE GROUP: A DUAL-MODEL APPROACH (Journal of Global Accounting, 2022)
Firms are expected to operate within acceptable standards of corporate governance for consistent profitable operations. Since adherence to governance practices is critical to winning and retaining customers’ confidence and patronage, the imperative for good governance practices as can be demonstrated in the composition of the boards cannot be overemphasized. Against this background, this study investigates the effect of board characteristics on financial performance of quoted Insurance companies in Nigeria from 2012-2020. The specific objectives are to find out how Board Size and Board Nationality Diversity affect financial performance using a bi-model analysis involving Tobin Q and return on asset (ROA) as response variables. Firm Size and Leverage Ratio were used as control variables. The population of the study is the same as the sample size comprising Twenty-two (22) Insurance companies in Nigeria. The data were analysed with the aid of random regression method. The results show that Board Size has insignificant positive effect on Tobin Q, but a significant positive effect on ROA, while, Board Nationality Diversity has a significant negative effect on Tobin Q, but an insignificant positive effect on ROA. The study recommends that Nigerian Insurance companies with large board should measure their performance with ROA, while, those companies with board of diverse nationalities should estimate their financial performance with Tobin Q
Keywords: Board Characteristics; Board Nationality Diversity; Board Size; Financial Performance; Return on Asset; Tobin Q